The origin of gley colors in hydromorphic vertisols : The study case of the coastal plain of the Río de la Plata estuary - Gómez Samus, Mauro Leandro (2021)
This work aims to contribute to the interpretation of soil colors; mainly to identify the pigments that generate the greenish colors in hydromorphic conditions (gley colors) in vertisols of the coastal plain of the Rio de la Plata estuary. These colors are of cold hues, generally greenish (olive-gray), and occur in poorly drained soils with prolonged water accumulation. For this purpose, samples of Bssg horizons of hydromorphic vertisols from the coastal plain of the Rio de la Plata estuary were analyzed using routine and chemical analyses, Mossbauer spectroscopy, determination of rocks magnetic parameters, X-ray diffraction, thermogravimetric and differential thermal analysis and petrographic-electronic microscopy. The pigments associated with the gley colors of these soils are mainly due to ferric iron content, corresponding to minerals such as ferric iron-rich smectites (nontronite/Fe-rich beidellite) and oxy-hydroxides like goethite, which colors range from green to yellow. These minerals, combined with gray or black components, e.g., manganese compounds and/or organic matter, contribute to the generation of the usual gley colors in the analyzed soils of the Pampean plain. The obtained data allows us to state that it is a mistake to assing the olive color in hydromorphic soils to the presence of ferrous iron compounds, as it is traditionally done. The oxidizing condition of iron is dominant in all the analyzed samples, integrating the composition of ferric iron-rich clay minerals and oxy-hydroxides (goethite).